Justification of Literature - Semab, Naseeb Ullah (sourcecoder, 2023)
Internally, man has a world inside himself. This world is his own. He adjusts it according to his pleasure. He gives it the colors of his pleasure. However, the inner world of man in another language, we call it the imaginary world. It has a different color from the real world or the external world. In this inner world of man, have his own thoughts, ideas, and concepts. He has realized that he is very different from the outside world. What is bitter in the outside world becomes sweeter in his inner world. This imaginary world of man is made in the light of human psychology. It is as if a new human being, when he enters this world, falls into a special psychological quality. From these internal qualities, a person gets psychological pleasure. Humans have common instincts. Instinct is the force that affects a person. It is not based on skills. These skills become on the basis of a person's personality in the form of human behavior. These instincts are sex, hunger, thirst, love, mother's love, father's love, and desires and so on. Scholars say that all these instincts are the common heritage of all human beings regardless of race or color. It is the inner instincts of man that create the license of literature. Man is forced to express his desires and wishes in such a way that he looks beautiful in the society. If he does not do it, he will not be accepted in the society. This is not what he is doing for the society, but he is doing it for his own psychological comfort. This psychological comfort is expressed.